Phenylation of azobenzene - Miller, Joseph; Paul, D.B.; Wong, L.Y.; Kelso, A.G. (Royal Society of Chemistry, 1970)
The substituent effect of the phenylazo-group in homolytic phenylation has been measured with azobenzene as substrate and nitrobenzene as reference compound. Even after allowance for the large number of sites of substitution the phenylazo-group was shown to equal the nitro-group in its activating power. Isomer ratios and partial rate factors have been determined and are discussed. © Royal Society of Chemistry.